KONTRIBUSI JOB DEMANDS DAN JOB RESOURCES TERHADAP PSYCHOLOGICAL WELL-BEING PEKERJA CREATIVE AGENCY DI JAKARTA - Hung, Nathalyn; Kembaren, Esther Muliana (MANASA, 2024)
This study aims to examine the contributions of job demands and job resources to the psychological well-being of creative agency workers. Creative agencies often require longer working hours and higher workloads to meet customer demands. However, the resources provided by companies to support workers sometimes do not adequately compensate for these demands, which can negatively impact workers' psychological well-being. Despite this, creative agencies depend heavily on their workers to achieve company targets, and the psychological well-being of these workers plays a crucial role in their ability to develop their potential and function optimally. It is predicted that adequate job resources to meet job demands will enhance the psychological functioning of workers. This research utilized quantitative methods and involved 106 creative agency workers in Jakarta, selected through convenience sampling. The instruments used for measurement were the Questionnaire sur les Ressources et Contraintes Professionnelles and the Psychological Well-Being Scale. The results of multiple regression analysis indicated that job demands and job resources significantly contribute to the psychological well-being of creative agency workers. Specifically, job demands have a negative impact on psychological well-being, whereas job resources have a positive impact. Therefore, even though the work is demanding, sufficient resources can help maintain the psychological well-being of workers.